Training on the Use of Google My Business as a Digital Marketing Medium for MSMEs in the Digitalization Era (Future Science, 2021)
The role of information and communication technology (ICT) in supporting UKMK during the COVID-19 pandemic is getting bigger, software as a service (SAAS) developers are also improving their services to help UMKM business processes. Google, one of the SAAS service providers, provides Google My Business products to help customers find business products from MSMEs, the change in people's buying styles through digital technology has been realized by Carving Gabus Surabaya (CGS), CGS is an MSME engaged in cork carving production services for wedding aisle decoration needs to other public events. The problem being faced by CGS is the lack of ability of owners and employees to operate ICT facilities to connect the marketing of CGS products and services to digitalization. Therefore, it is necessary to conduct training related to the creation and management of Google My Business for CGS owners and employees, the aim is to provide stimulants and training to MSME activists. Based on the results of the evaluation of activities, there is an alignment between the need to know the use of Google My Business and the usefulness of using Google My Business for CGS marketing towards digitalization.